Aboveground and belowground responses to cyanobacterial biofertilizer supplement in a semi‐arid, perennial bioenergy cropping system. Issue 12 (3rd October 2021) - Goemann, Hannah M.; Gay, Justin D.; Mueller, Rebecca C.; Brookshire, E. N. J.; Miller, Perry; Poulter, Benjamin; Peyton, Brent M.
Abstract: The need for sustainable agricultural practices to meet the food, feed, and fuel demands of a growing global population while reducing detrimental environmental impacts has driven research in multi‐faceted approaches to agricultural sustainability. Perennial cropping systems and microbial biofertilizer supplements are two emerging strategies to increase agricultural sustainability that are studied in tandem for the first time in this study. During the establishment phase of a perennial switchgrass stand in SW Montana, USA, we supplemented synthetic fertilization with a nitrogen‐fixing cyanobacterial biofertilizer (CBF) and were able to maintain aboveground crop productivity in comparison to a synthetic only (urea) fertilizer treatment. Soil chemical analysis conducted at the end of the growing season revealed that late‐season nitrogen availability in CBF‐supplemented field plots increased relative to urea‐only plots. High‐throughput sequencing of bacterial/archaeal and fungal communities suggested fine‐scale responses of the microbial community and sensitivity to fertilization among arbuscular mycorrhizal fungi, Planctomycetes, Proteobacteria, and Actinobacteria. Given their critical role in plant productivity and soil nutrient cycling, soil microbiome monitoring is vital to understand the impacts of implementation of alternative agricultural practices on soil health. Abstract : The biofertilizer potential of N‐fixing cyanobacterium Anabaena cylindrica on Panicum virgatum (switchgrass) stand establishment was assessed in a semi‐arid, perennial bioenergy cropping system. Results showed biofertilizer application promoted similar plant growth as chemically fertilized P. virgatum and increased late‐season soil N‐availability without having strong effects on the soil microbial community composition or diversity. Combining perennial bioenergy crops and biofertilization could significantly improve agricultural sustainability by improving nutrient retention and maintaining microbially‐mediated ecosystem processes. These results provide a foundation for further implementation of biofertilizers in perennial bioenergy cropping systems.